Activity of moxalactam and cefotaxime alone and in combination with ampicillin or penicillin against group B streptococci. - Landesman, S H (1981)
The activities of moxalactam and cefotaxime, alone and combined with ampicillin or penicillin, against 40 isolates of group B streptococci were assessed by using the microtiter broth dilution, checkerboard, and time-kill techniques. Penicillin and cefotaxime were bactericidal for all isolates at concentrations of 0.06 micrograms/ml or less. Ampicillin was slightly less active. Moxalactam was bactericidal for all strains at concentrations of 4 to 8 micrograms/ml. The ampicillin- moxalactam combination was partially synergistic for 60% of the isolates tested; the ampicillin-cefotaxime combination was partially synergistic for 35% of these isolates. No instances of antagonism were observed. In time-kill evaluations, ampicillin (3.0 micrograms/ml) and penicillin (0.75 micrograms/ml) effected 2.5 to 3.5 log10 reductions in numbers of colony-forming units. The addition of 4 micrograms of cefotaxime per ml or 8 to 16 micrograms of moxalactam per ml to penicillin or ampicillin did not alter killing kinetics. Moxalactam and cefotaxime neither enhanced nor decreased the activity of ampicillin or penicillin against group B streptococci.